AmpliVar: Mutation Detection in High‐Throughput Sequence from Amplicon‐Based Libraries. Issue 4 (16th March 2015) - Hsu, Arthur L.; Kondrashova, Olga; Lunke, Sebastian; Love, Clare J.; Meldrum, Cliff; Marquis‐Nicholson, Renate; Corboy, Greg; Pham, Kym; Wakefield, Matthew; Waring, Paul M.; Taylor, Graham R.
<x xml:space="preserve">Abstract</x> In this study, AmpliVar was applied to amplicon sequencing data derived from acute myeloid leukemia, breast and ovarian cancer samples. Using a grouped read and quality filtering approach, AmpliVar identified variants with the highest sensitivity and effective false positive reduction. It displayed superior processing speed and was able to be used as an orthogonal means of validation for hybridization capture data. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>